Government Colonial Policy and Indigenous Organizations in The Field of Health in Surabaya 1900-1939 - Mariyatul Hakim, Noviani (Riviera Publishing, 2023)
The purpose of this research is to determine the role of indigenous organizations and Dutch government policies as the implementing authority in addressing diseases that affected the community from 1900 to 1939 in Surabaya. This research study employs a historical method consisting of Heuristics (source collection), Source Criticism, Interpretation, and finally Historiography (presentation of data in written form). Based on the research findings and data sources obtained, it is revealed that the policies issued by the colonial government were the result of the involvement of intellectual figures and private organizations who actively conveyed criticisms. The research findings discovered that throughout its course, the colonial government collaborated with educated indigenous figures to promote a healthy lifestyle. In addition to establishing hospitals and health centers, the improvement of public health focused on preventive measures, such as promoting clean living habits among the community. The final results of this research indicate that the government's success in curbing the spread of diseases was not solely achieved through its own efforts, but through collaboration between the government, private parties, and the community.